2015
DOI: 10.1007/s10964-015-0342-9
|View full text |Cite
|
Sign up to set email alerts
|

Victim Reports of Bystander Reactions to In-Person and Online Peer Harassment: A National Survey of Adolescents

Abstract: Bullying prevention is increasingly targeting education to bystanders, but more information is needed on the complexities of bystander actions across a wide variety of incidents, including both online and in-person peer harassment. The current study analyzes victim report data from a nationally representative survey of youth ages 10-20 (n = 791; 51% female). Bystander presence was common across all harassment incident types (80% of incidents). In contrast to previous research, our study found that supportive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 22 publications
1
53
1
4
Order By: Relevance
“…As young people increasingly associate online with people that they also know offline, the fluidity of these roles has received more attention in recent years (Festl et al ., ; Quirk and Campbell, ) with some acknowledgement that the norms negotiated in an offline setting often influence an individual's online behaviour (Seiler and Navarro, ; Jones et al ., ). Indeed, the role of social hierarchies in involuntary social groups, such as school classes, has been raised as an area of note (Festl et al ., ) in terms of the degree to which a cyberbullying event impacts upon pre‐existing social group dynamics and individual social identity.…”
Section: A Review Of the Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…As young people increasingly associate online with people that they also know offline, the fluidity of these roles has received more attention in recent years (Festl et al ., ; Quirk and Campbell, ) with some acknowledgement that the norms negotiated in an offline setting often influence an individual's online behaviour (Seiler and Navarro, ; Jones et al ., ). Indeed, the role of social hierarchies in involuntary social groups, such as school classes, has been raised as an area of note (Festl et al ., ) in terms of the degree to which a cyberbullying event impacts upon pre‐existing social group dynamics and individual social identity.…”
Section: A Review Of the Literaturementioning
confidence: 97%
“…It has been argued that insufficient attention has been paid to the contextual determinants of cyberbullying, and the actors involved (Bastiaensens et al ., ; Shultz et al ., ), and that more research is needed to better understand the complexities of bystander behaviours (Jones et al ., ). Moreover, Shultz et al .…”
Section: Introductionmentioning
confidence: 97%
“…Although research on this topic is limited, among college students who had been bullied prior to college, friend social support during college buffered the effect of prior bullying on anxiety over time (Reid et al 2016). Research in adolescence also demonstrated that victims who were defended were better adjusted and reported less depression than those who were not defended (Jones et al 2015;Ma and Chen 2017;Sainio et al 2010). Because of the prevalence of bullying among college students and the possible negative effects on adjustment to college, it is important to understand which factors predict students supporting their victimized peers in helpful, prosocial ways and which individuals may be at risk for defending their victimized peers in ways that continue the cycle of aggression among college students.…”
Section: Peer Victimization Among College-aged Studentsmentioning
confidence: 99%
“…These include which activities and venues comprise electronic bullying (Vandebosch and Van Cleemput 2009), whether defining attributes of bullying such as intent to harm, power imbalance and repetition should also be applicable to electronic bullying (Patchin and Hinduja 2015), and how electronic bullying should be addressed by schools and school-based bullying interventions (Bauman and Bellmore 2015). Similar constructs to electronic bullying that have been studied among adolescents include online harassment (e.g., Jones et al 2015, online aggression (e.g., Law et al 2010, aggressive forum posts (e.g., Moore et al 2012), and negative online peer feedback (e.g., Koutamanis et al 2015).…”
Section: Involvement With Social Mediamentioning
confidence: 99%